Traditional urban configuration of the Kota Bharu, Kelantan in the seventeenth CE - Ibrahim, Illyani (2020)
This map shows royal elements of traditional urban configuration of palace and fort, river, masjid, padang and market in Kota Bharu, Kelantan. The palace is so close to the mosque. Padang elongated to the river. The old settlement and market are also located near to the river. The administration areas are located near to the mosque.